Study of the dynamic fracture characteristics of coal with a bedding structure based on the NSCB impact test. (15th October 2017) - Wang, Yanbing; Yang, Renshu
Highlights: Test dynamic toughness of rock. The DLSM model were used. A high-speed camera records and observes the coal sample's dynamic fracture process. The distinct lattice spring model (DLSM) numerical analysis method is applied to preliminarily analyze the sample dynamic splitting process and the change in the stress field. The influence of the impact velocity, bedding angle, elastic modulus of bedding medium, bedding spacing and bedding width on the KIC test results are quantitatively analyzed. Abstract: To study the dynamic fracture deformation and failure characteristics of coal samples, the split Hopkinson bar (SHPB) impact loading system is used to test the dynamic fracture toughness of coal samples based on the notched semi-circular bend (NSCB) method under an impact load. The influence of the impact velocity and bedding angle on the dynamic fracture toughness, failure strain and strain rate of coal samples is preliminarily discussed, and a high-speed camera records and observes the dynamic fracture process of the coal sample. Finally, the distinct lattice spring model (DLSM) numerical analysis method is applied to analyze the sample dynamic splitting process and the change in the stress field. Meanwhile, the influences of the impact velocity, bedding angle, elastic modulus of bedding medium, bedding spacing and bedding width on the KIC test results are quantitatively analyzed.